Low Brain Iron Effects and Reversibility on Striatal Dopamine Dynamics - Unger, Erica L. (Exp Neurol, 2014)
Iron deficiency (ID) in rodents leads to decreased ventral midbrain (VMB) iron concentrations and to changes in the dopamine (DA) system that mimic many of the dopaminergic changes seen in RLS patient where low substantia nigra iron is a known pathology of the disease. The ID-rodent model, therefore, has been used to explore the effects that low VMB iron can have on striatal DA dynamics with the hopes of better understanding the nature of iron-dopamine interaction in Restless Legs Syndrome (RLS). Using a post-weaning, diet-induced, ID condition in rats, the No-Net-Flux microdialysis technique was used to examine the effect of ID on striatal DA dynamics and it reversibility with acute infusion of physiological concentrations of iron into the VMB. This study replicated prior findings by showing that the ID condition is associated with increased extracellular striatal DA, reduced striatal DA uptake, and blunted DA-2-receptor-agonist feedback enhancement of striatal DA uptake. Despite the increase in extracellular striatal DA, intracellular striatal DA, as determined in tissue homogenates, was decrease in the ID rat. The study’s key finding was that an infusion of physiological concentrations of iron into the VMB reversed the ID-induced increase in extracellular striatal DA and the ID-induced decrease in intracellular striatal DA but had no effect on the ID-induced changes in DA uptake or on the blunted DA-uptake response to quinpirole. In summary, the ID-rodent model provides highly reproducible changes in striatal DA dynamics that remarkably parallel dopaminergic changes seen in RLS patients. Some but not all of these ID-induced changes in striatal DA dynamics were reversible with physiological increases in VMB iron. The small changes in VMB iron induced by iron infusion likely represent biologically relevant changes in the non-transferrin-bound labile iron pool and may mimic circadian-dependent changes that have been found in VBM extracellular iron.